CASE-STUDY METHOD IN PREPARING FUTURE MATHEMATICS TEACHERS - Shmigirilova, И.; Chugunova, А.; Beloshistova, Я.; Dutkin, М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
In the structure of the professional competence of a mathematics teacher, a special role is played by knowledge called «mathematical knowledge for learning». In the formation of such a system of knowledge, as well as the skills and abilities associated with it, a great contribution, in addition to methodological courses, is made by disciplines aimed at repeating and systematizing school mathematics. The purpose of the article is to update the effectiveness of the case-study method as a means of forming students, future teachers of mathematics, a knowledge system of elementary mathematics and their didactic content. Theoretical and empirical data obtained in the course of the study and reflected in the article prove that the use of the case method in the university training of a school mathematics teacher creates conditions for the formation of both knowledge of elementary mathematics and knowledge of their didactic content, which is necessary for a school teacher of mathematics.